Physical Activity and Student Satisfaction Level of MURI Record SKJ 2022 - Sahdi kadir, Sulasikin; Pomatahu, Aisah R.; Pauweni, Mirdayani; Ndayisenga, Japhet; Cahyuji Ganny, Rochmad; Bin Seh Abubakar, Sayid Fariz (Universitas Muhammadiyah Enrekang, 2025)
The level of satisfaction of participants at the launching of the SKJ 2022 muri record held by the Menpora has a relationship with the physical activity of students, so the purpose of this study was to determine the level of satisfaction and physical activity of the SKJ 2022 muri record. The type of research used was descriptive research, the population in this study was all students from both elementary, junior high, and high school/vocational school in Gorontalo Province, and the sample is 823 respondents. The sampling technique uses Accidental Sampling. The data collected is based on a questionnaire that is distributed via Google Forms. The satisfaction level of the participants was 38.64% in the very satisfied category, 60.87% in the satisfied category, 0.49% in the dissatisfied category, and 0% in the very dissatisfied category. Based on the results of the study: 1) the level of student satisfaction following the SKJ 2022 muri record is in the